Fibrillin-1 and alpha8 integrin are co-expressed in the glomerulus and interact to convey adhesion of mesangial cells - Marek, Ines; Volkert, Gudrun; Hilgers, Karl Friedrich; Bieritz, Beate; Rascher, Wolfgang; Reinhardt, Dieter P.; Hartner, Andrea (Cell Adhesion and Migration, 2014)
Fibrillin-1 is a microfibrillar extracellular matrix protein that was described to be a ligand for ?8 integrin. ?8 integrin is a matrix receptor specifically expressed in mesangial and smooth muscle cells of the kidney. In previous studies we detected glomerular expression of fibrillin-1. Moreover, fibrillin-1 promoted adhesion, migration, and proliferation of mesangial cells. We hypothesized that fibrillin-1 and ?8 integrin might interact in the glomerulus, and thus, regulate mesangial cell properties. Our studies showed that fibrillin-1 and ?8 integrin colocalize in the glomerular mesangium. Induction of experimental glomerulonephritis led to an increase of both fibrillin-1 and ?8 integrin expression. In vitro studies revealed that mesangial cells deficient for ?8 integrin adhere weaker to fibrillin-1 and migrate more easily on fibrillin-1 than wild-type mesangial cells. Baseline proliferation on fibrillin-1 is higher in ?8 integrin-deficient mesangial cells, but the induction of proliferation is not different in ?8 integrin-deficient and wild-type mesangial cells. We conclude that fibrillin-1 and ?8 integrin interact, and thus, regulate mesangial cell adhesion and migration. The concomitant induction of both fibrillin-1 and ?8 integrin in a self-limited model of glomerular injury points to a protective role of the interaction of fibrillin-1 with ?8 integrin in the glomerulus resulting in reduced damage of the glomerular tuft as a consequence of firm adhesion of mesangial cells.
EVALuna2:3751